Criminal Sanctions in the Application of Electronic Ticketing Using CCTV (Closed Circuit Television) Recording by Satlantas Polda Maluku Utara - Muhammad Mufti; Dewi Suyatni; Faisal Faisal (Khairun Law Journal, 2021)
This study aims to determine how the criminal sanctions against electronic traffic ticket offenders using CCTV (Closed Circuit Television) recordings and what obstacles are experienced by the North Maluku Regional Police in the application of electronic ticket penalties using CCTV (Closed Circuit Television) recordings. The type of research used in this research is empirical normative research type. Location This research was conducted at the North Maluku Police Traffic Unit. In addition, researchers also conducted direct interviews with the community regarding the application of electronic ticketing by the North Maluku Police Traffic Unit which was recently implemented in Ternate City. Then, the data obtained were analyzed descriptively qualitatively. Based on the pre-research conducted by researchers, the e-ticket system used by the North Maluku Police Traffic Police is regulated in article 272 of Law number 22 of 2009 concerning road traffic and transportation, the application of e-ticketing through CCTV footage is not yet fully effective because it has only been implemented in one city out of 10 municipalities in North Maluku Province, namely Ternate City, and is still in the socialization period, but what researchers highlight is the application of e-ticketing penalties that have not been clearly regulated by the traffic law. How are the criminal sanctions applied by the North Maluku Police Traffic Unit, if the vehicle recorded by CCTV is not the legal owner listed on the vehicle registration documents (Vehicle Registration Certificate), how is the application of traffic penalties against vehicles or offenders who are sanctioned criminal. One of the principles of criminal law is that there is no crime without error, that a person can only be punished for his actions if there is an error in himself. Whether the offender driving the vehicle at that time, not the legal owner of the vehicle listed on the vehicle registration certificate, is given a criminal sanction. Or is it the owner of the vehicle who must be responsible for the negligence of the offender? The obstacle experienced by the North Maluku Police Traffic Unit is the absence of a traffic regulation that clearly regulates e-ticketing penalties